Evaluasi UI/UX Website Pemesanan Tiket Wayang Orang Sriwedari Surakarta Berdasarkan Hasil Pengujian System Usability Scale (SUS) dan User Experience Questionnaire (UEQ) - Febriana Nur Aini; Nur Widjiyati; Eko Pramono; Wiji Nurastuti; Rum Andri; Ahmad Sumiyanto (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
Wayang Orang Sriwedari (WOS) is one of the traditional performance icons originating from the city of Surakarta. The ticket booking process, which previously lacked proper digitalization, generated various complaints, such as limited information and the lack of flexibility for visitors in selecting seats. This study focuses on testing the user interface design of the Wayang Orang Sriwedari ticket booking website to quantitatively assess its usability and user experience. The evaluation was conducted using the System Usability Scale (SUS) and the User Experience Questionnaire (UEQ) through online questionnaires distributed via Google Forms. The testing involved 35 respondents representing potential users of the system. The results show an average SUS score of 86.14, which falls into the “A+” grade category. The UEQ evaluation produced positive results, categorized as “Excellent” for the aspects of attractiveness, clarity, efficiency, accuracy, and stimulation, and “Good” for the novelty aspect. These findings indicate that the website interface design meets the criteria for excellent usability and provides a positive user experience, making it feasible for implementation in the Wayang Orang Sriwedari ticket booking system.